Basics of Neuropharmacology - Zeise-Ssa., M (Springer International Publishing, 2020)
Neuropharmacology deals with specific and unspecific interactions of substances with diverse molecules of the nervous system. Starting with the chemical elements, the various intermolecular bonds are presented together with symmetric vs. asymmetric electron distribution leading to lipophilic or hydrophilic interactions. These lead to hydrogen bonds that, together with other weak attractive forces, come into play when reversible molecular interaction is dealt with, such as the one between ligand and receptor, but that also help to explain the folding of biological macromolecules. Then basic pharmacological concepts, such as agonism, antagonism, and partial agonism, as well as affinity, efficacy, and potency are described. This chapter concludes with a thorough description of molecular targets at the synapse and a comparison between ionotropic and metabotropic receptors. © Springer Nature Switzerland AG 2021.